2019
DOI: 10.1038/s41598-019-55918-w
|View full text |Cite
|
Sign up to set email alerts
|

Interpretation of detections of volcanic activity at Ioto Island obtained from in situ seismometers and remote hydrophones of the International Monitoring System

Abstract: In-situ seismic observations identified that volcanic activity of Ioto (formerly Iwojima), a volcanic island offshore Japan, increased in early September 2018. Observations of discolored nearshore waters and a splash reported by a local flyover provided evidence for a connection between undersea eruptions and recorded seismic activity. However there remain uncertainties as to when the undersea eruption series commenced and how much of the in-situ seismic activity recorded on the island was associated with volc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
22
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 13 publications
(23 citation statements)
references
References 53 publications
1
22
0
Order By: Relevance
“…TR2 did not accompany apparent infrasound signals. Matsumoto et al (2019) reported that remote hydrophones detected no relevant signal on September 12, either, even though small splashes were observed in shallow water near the Okinahama coast. Explosions under shallow water and violent water jets into the air generate detectable infrasound signals (Ichihara et al 2009;Lyons et al 2019Lyons et al , 2020, but those were not detected in this case.…”
Section: Volcanic Activity Associated With Tr1 and Tr2mentioning
confidence: 99%
See 3 more Smart Citations
“…TR2 did not accompany apparent infrasound signals. Matsumoto et al (2019) reported that remote hydrophones detected no relevant signal on September 12, either, even though small splashes were observed in shallow water near the Okinahama coast. Explosions under shallow water and violent water jets into the air generate detectable infrasound signals (Ichihara et al 2009;Lyons et al 2019Lyons et al , 2020, but those were not detected in this case.…”
Section: Volcanic Activity Associated With Tr1 and Tr2mentioning
confidence: 99%
“…The island, about 8 km × 4 km in size with the highest elevation of 170 m, is just the summit part of a stratovolcano rising about 2000 m from the sea floor. Eruptions sometimes occur under the sea and are detected by remote hydrophones (Matsumoto et al 2019). The seismic activity is intense and a large-scale uplift has continued for centuries (Kaizuka et al 1985;Ueda et al 2018).…”
Section: Volcanic Activities At Ioto Island In 2013 and 2018mentioning
confidence: 99%
See 2 more Smart Citations
“…Ioto is an isolated volcanic island of which seismicity is regularly intense (Ueda et al 2018). At Ioto, phreatic eruptions frequently occur due to the high geothermal activity (Notsu et al 2005), and the volcanic activity is pronounced not only on the ground but also undersea detected by remote hydrophones (Matsumoto et al 2019). In this situation where the volcanic activity is very high throughout the island, there is a need to monitor eruptions and its temporal changes.…”
Section: Introductionmentioning
confidence: 99%